Hemodynamic Response to the Head-Up Tilt Test in Patients With Syncope as a Predictor of the Test Outcome: A Meta-Analysis Approach - Buszko, Katarzyna; Kujawski, Sławomir; Newton, Julia L.; Zalewski, Paweł (Frontiers in Physiology, 2019)
Aim: The paper presents a meta-analysis of studies comparing hemodynamic parameters: heart rate (HR), systolic blood pressure (sBP), diastolic blood pressure (dBP), and stroke volume (SV) measured during head-up tilt table test (HUTT) in patients with positive and negative HUT test outcome. Methods: Pubmed and Clinical Key databases were searched for English-only articles presenting results of biosignals measurements during tilt test in patients suffering from syncope. From 3,289 articles 13 articles published between 1997 and 2015 investigating 892 patients (467 with positive HUTT outcome and 401 with negative one) were selected. Results: There were not statistically significant differences observed between the parameters measured in supine position in patients with positive and negative test outcome [HR (p = 0.86), sBP (p = 0.32), dBP (p = 0.21), SV (p = 0.71)]. In tilt position the parameters HR and SV were significantly different when compared between the two groups of patients [HR (p = 0.02), sBP (p = 0.10), dBP (p = 0.59), SV (p = 0.0004)]. Conclusions: Changes in HR and SV parameters in response to tilt test turned out to be statistically significant. In supine position the differences between patients with positive and negative test outcome were not significant, hence tilt test can be considered as necessary in the diagnosis of vasovagal syndrome.